Humouring Futurity: Avant-Garde Poetry for Children?. Issue 3 (September 2021) - Dorkin, Andrew
Abstract : This essay humours the possibility of a kinder-garde, in which poets humour children so that children might humour poetry's futurity. I propose humouring as a critical approach premised on a compliant tension with a text, a subversive toleration that undermines 'aetonormative' seriousness and upholds 'childish' humour as valuable play-with-value. The Kindergarde anthology (ed. Dana Teen Lomax 2013 ) claims to translate avant-gardism for a child audience, linking its experimental poems to the experimentation of children's play. Using carnivalisation, détournement, defamiliarisation, and other forms of what Ryan Fitzpatrick and Jonathan Ball term 'experimentation-with-humour', Kindergarde constructs inclusive spaces for humoured subversion, in which children can sidestep oppressive adult normativity. The child's humoured humouring of adult power is discussed here by re-reading children's literature's 'impossible relation' (after Jacqueline Rose) in terms of Michel Serres' 'parasite', Judy Little's feminist 'humouring' of male language, and Lee Edelman's queering of 'reproductive futurism.' Asserting that it is the condition of twenty-first-century poetry to be humoured – as a 'minor literature' (Deleuze and Guattari) with a 'minor attitude' (Georges Bataille) – my humouring of the Kindergarde builds toward a post-literary vision of the kinder-gardist as futurity-humourist.